Higher G allele frequency of RET C2307t>G polymorphism in female patients with Hirschsprung disease in Yogyakarta, Indonesia - Ahmad Hamim Sadewa; Saryono Saryono; Rochadi Rochadi; Wiryatun Lestariana; Wayan T Artama (Indonesian Pediatric Society Publishing House, 2008)
Background Hirschsprung disease (HSCR) is a heterogenous congenital disorder and the current research show that the RET gene is a major locus involved in its pathogenesis. However, whether these genes take a part in sporadically Indonesian HSCR have not been fully understood. Objective The aim of this study was to analyze the association of RET gene c2307T>G polymorphism among HSCR patient in Yogyakarta population. Methods Genomic DNA was extracted from bowel tissues of 34 patients with sporadic HSCR which were removed by surgery as case group and blood DNA from 46 healthy persons as control group without history of genetic disorder. Exon 13 of RET gene was amplified by polymerase chain reaction (PCR) and was analyzed by restriction fragment length polymorphism (RFLP). Results Of 34 patients, 22 were males and 12 were females, giving male to female ratio of 1.83:1. The c2307T>G polymorphism in RET exon 13 was not significantly difference between patient and control group (chi-square test P=0.17). However, there was a significant difference in female patient compare with control (chi-square test P=0,04). Conclusion The RET gene c2307T>G polymorphism was found among HSCR patient in Yogyakarta population. This poly- morphism can be used as predictor for development of HSCR among female individual.